Mapping OMIM Disease–Related Variations on Protein Domains Reveals an Association Among Variation Type, Pfam Models, and Disease Classes - Savojardo, Castrense; Babbi, Giulia; Martelli, Pier Luigi; Casadio, Rita (Frontiers in Molecular Biosciences, 2021)
Human genome re-sequencing projects provide an unprecedented amount of data about single- nucleotide variations occurring in protein-coding regions and often leading to observable changes in the covalent structure of gene products. For many of these variations links to OMIM genetic diseases are available and reported in many databases collecting human variation data such as Humsavar. However, our current knowledge on the molecular mechanisms leading to disease is, in many cases, still limited. For understanding the complex mechanisms behind disease insurgence, the identification of putative models considering protein structure and chemico-physical features of the variations can be useful in many contexts, including early diagnosis and prognosis. Here, we investigate the occurrence and distribution of human disease-related variations in the context of Pfam domains. The aim of this study is the identification and characterization of Pfam domains that are statistically more likely to be associated with disease-related variations. The study takes into consideration 2513 human protein sequences with 22763 disease-related variations. We describe an analysis of patterns of disease-related variation types in biunivocal relation with Pfam domains and therefore likely to be possible markers for linking Pfam domains to OMIM diseases. Furthermore, we take advantage of the specific association between disease-related variation type and Pfam domains for clustering diseases according to the Human Disease Ontology and we establish a relation among variation types, Pfam domains and disease classes. We find that Pfam models are specific markers of patterns of variation types and that they can serve to bridge genes, diseases and disease classes. Data are available as supplementary material for 1670 Pfam models including 22763 disease related variations associated to 3257 OMIM diseases.